2012
DOI: 10.1073/pnas.1210882109
|View full text |Cite
|
Sign up to set email alerts
|

The T-cell receptor is not hardwired to engage MHC ligands

Abstract: The bias of αβ T cells for MHC ligands has been proposed to be intrinsic to the T-cell receptor (TCR). Equally, the CD4 and CD8 coreceptors contribute to ligand restriction by colocalizing Lck with the TCR when MHC ligands are engaged. To determine the importance of intrinsic ligand bias, the germ-line TCR complementarity determining regions were extensively diversified in vivo. We show that engagement with MHC ligands during thymocyte selection and peripheral T-cell activation imposes remarkably little constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…We expanded on this here by demonstrating that, in the structural database of TCRs that bind HLA-A2, not only are there no conserved TCR-MHC contacts, even those amino acids in TCR germ-line loops that are the least variable make different contacts or do not contact A2 at all. These results are consistent with findings that diversified TCRs can still bind MHC (35), and prompted us to search for a more fundamental basis for MHC bias based upon compatibility rather than simply contacts. Through a combination of sequence, structural, and biophysical analyses, we demonstrated that TCR germ-line loops are enriched in the means to complement a polymorphic hot-spot region on the α1-helix of the class I MHC protein HLA-A2, consisting of positively charged residues that are absent from most other HLA-A alleles, as well as those of HLA-B and HLA-C. Burial of these charges is required for TCRs to sample peptides effectively, and without the ability to complement them, their burial would be highly unfavorable due to the energetic cost of desolvation (26,27).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We expanded on this here by demonstrating that, in the structural database of TCRs that bind HLA-A2, not only are there no conserved TCR-MHC contacts, even those amino acids in TCR germ-line loops that are the least variable make different contacts or do not contact A2 at all. These results are consistent with findings that diversified TCRs can still bind MHC (35), and prompted us to search for a more fundamental basis for MHC bias based upon compatibility rather than simply contacts. Through a combination of sequence, structural, and biophysical analyses, we demonstrated that TCR germ-line loops are enriched in the means to complement a polymorphic hot-spot region on the α1-helix of the class I MHC protein HLA-A2, consisting of positively charged residues that are absent from most other HLA-A alleles, as well as those of HLA-B and HLA-C. Burial of these charges is required for TCRs to sample peptides effectively, and without the ability to complement them, their burial would be highly unfavorable due to the energetic cost of desolvation (26,27).…”
Section: Discussionsupporting
confidence: 80%
“…Only a single H 0 site in the TCR germ-line loops was identified, the histidine at position 29 in CDR1β, whose presence has been noted previously and is thought to be involved in loop organization (35). Five H 1 sites were identified, one each in CDR1α, CDR2α, and CDR1β, and two in CDR2β.…”
mentioning
confidence: 94%
“…An extension to this TCR hard-wiring concept is the "interaction codon hypothesis" pertaining to TCR-pMHC interactions, which posits that conserved pairwise interaction motifs between the germline-encoded regions of the TCR and the MHC underpin this TCR-MHC co-evolution (Adams et al, 2016). In contrast to the germline model, the selection model argues that MHC restriction is not an intrinsic feature of TCRs but is conferred by selection events in the thymus (Holland et al, 2012;Van Laethem et al, 2013). Here we show that the two TRBV17 + TCRs, which are found within the naïve T cell repertoire in wild type mice, adopt a reversed TCR-pMHC-I docking topology.…”
Section: Discussionmentioning
confidence: 99%
“…As for the TR, evolutionarily conserved features of the CDR1 and CDR2 of several TRBV genes have been proposed to enable a conserved docking mode of the TR onto the classical MH (23), although this remains controversial (24,25). For TRA, the analysis is complex because the number of TRAV genes may be very large, with multiple subgroups and wide variation across species (≈50 to >350 within mammals).…”
Section: Significancementioning
confidence: 99%